Effect of Xiongmatang Extract on Behavioral and TRPV1-CGRP/CGRP-R Pathway in Rats With Migraine - Liu, Dingding; Chang, Lulu; Wang, Jingru; Zhu, Qiang; Jiang, Ning; Azhar, Mudassar; Ahmed, Ayaz; Zeng, Guirong (Frontiers in Pharmacology, 2022)
Migraine is a complex neurovascular disease, which seriously affects the quality of life in patients. This study aimed to evaluate the effect of XMT extract on rats with migraine induced by inflammatory soup and the underlying mechanisms. First, one week after dural catheterization, inflammatory soup was injected through a microsyringe to stimulate the dura of rats for six times (two weeks), ten μL each time, to establish a migraine model. According to the macroscopic manifestations, pain threshold analysis, behavioral change detection, and pathological analysis, the effects of XMT extract on rats with migraine were evaluated. The positive, mRNA and protein expression of related factors were detected by immunohistochemistry, RT-QPCR, and Western blot analysis to elucidate the underlying mechanism. XMT extract improved the macroscopic and behavioral performance of rats, and improve the pathological changes in the trigeminal nerve in rats. Further experimental results show that XMT extract regulated the expression of migraine-related factors in the trigeminal nerve, manifested as TRPV1, CGRP, calcitonin receptor-like receptor (CRLR), and receptor activity-modifying protein 1 (RAMP1) positive expression, mRNA expression, and protein expression reduction. XMT extract can significantly improved the macroscopic features and behavioral performance of rats with migraine, and its mechanism of action might involve regulating the activity of TRPV1-CGRP/CGRP-R pathway.